1976
DOI: 10.1177/030098587601300304
|View full text |Cite
|
Sign up to set email alerts
|

Gnotobiotic Piglets Experimentally Infected with Neonatal Calf Diarrhoea Reovirus-Like Agent (Rotavirus)

Abstract: Abstract. Gnotobiotic piglets were infected with a strain of rotavirus that had been isolated from a calf and passaged four times in piglets. The resulting disease was studied by light and electron microscopy at 21,44 and 68h after inoculation. In thesmall intestine infection caused desquamation of the epithelial cells of the villi resulting in severe stunting. There was severe damage to microvilli and accumulation of lipid within the cytoplasm. Virus particles were seen in epithelial cells covering the stunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…It should be noted that the properties attributed to the faecal bovine rotaviruses referred to by Woode et al (1974), Woode (1975) andHall et al (1976) were due to a mixture of antigenically and pathogenically different viruses, some of which are described in this paper. It is possible that, as rotaviruses have segmented genomes, genetic reassortment, either before or after passage in experimental animals, had occurred between the viruses.…”
Section: Discussionmentioning
confidence: 59%
“…It should be noted that the properties attributed to the faecal bovine rotaviruses referred to by Woode et al (1974), Woode (1975) andHall et al (1976) were due to a mixture of antigenically and pathogenically different viruses, some of which are described in this paper. It is possible that, as rotaviruses have segmented genomes, genetic reassortment, either before or after passage in experimental animals, had occurred between the viruses.…”
Section: Discussionmentioning
confidence: 59%
“…It originated from an outbreak of diarrhoea in cattle, was pathogenic for pigs at the first passage (Hall et al 1976) and was found to be related antigenically to both bovine and porcine rotaviruses . On subsequent serial passage of the faecal PP-1 from gnotobiotic pigs in calves, it was avirulent but its pathogenicity for calves may have been modified by passage in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed pathogenesis studies of HRV infection in animals are few and limited to virulent HRV strains (Gouvea et al, 1986;Mebus et al, 1977). The reported pathological lesions induced by virulent strains of HRV in animals are similar to those induced by virulent rotaviruses of homologous host origin and include the loss of intestinal absorptive cells and villous atrophy followed by crypt hyperplasia and mucosal epithelium repair (Collins et al, 1989;Hall et al, 1993;Theil et al, 1978;McAdaragh et aI., 1980;Castrucci et al, 1983;Snodgrass et al, 1977;Adams & Kraft, 1967;Pappenheimer & Enders, 1947;Hall et al, 1976;Pearson & McNulty, 1977;Crouch & Woode, I978).…”
Section: 1980) the Experimental Infection Of A Speciesmentioning
confidence: 99%
“…The group A rotaviruses cause mild asymptomatic infection to severe life-threatening diarrhoea in susceptible hosts (Greenberg et al, 1994;Saif, 1990 b). Variations exist in prevalence and virulence among the group A rotaviruses which may account for the spectrum of disease observed among natural hosts (Collins et al, 1989, Greenberg et al, 1994Hall et al, 1976;Theil, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation